UPAYA UNITED NATIONS WORLD TOURISM ORGANIZATION (UNWTO) MENANGANI SEX TOURISM DI THAILAND (2009-2013) - Raesa Oktavia; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explain about the efforts of United Nations World Tourism Organization (UNWTO) in dealing with sex tourism in Thailand. This research focused explaining about the role of UNWTO to fix sex tourism problem in Thailand, because sex tourism is one of the most favorite tourism in the world. UNWTO focused to protect the children because they are the biggest victim on sex tourism. This research intended to show the role of United Nations World Tourism Organization to handle the sex tourism in Thailand. UNWTO did some cooperation with Thailand Government and some international organization also with non-governmental organization. Attempts have been made from UNWTO by establish children protection, however UNWTO cannot get into the sex tourism sector adulthood and transgender because there are so much obstacles related to human rights.Keywords : Effort, UNWTO, Sex Tourism, Human Trafficking and Prostitution